Analysis of School Administrative Service Quality Using SERVQUAL Model in SMA Negeri 19 Batam - Firdaus, Fadli; Fajrina, Nadhilah Nur; Syafrina, Mia (PT Aksara Indo Rajawali, 2025)
School administration service is essential in supporting the effectiveness of education management. This study aims to analyze the service quality of administrative staff at SMA Negeri 19 Batam based on students' perceptions, using the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. The qualitative approach with an interpretive-phenomenological paradigm involved in-depth interviews with four purposively selected students. The results showed that the quality of administrative services is still not optimal. The main problems identified include limited physical facilities, shortage of administrative staff, inflexible service procedures, and lack of empathy and friendliness in service interactions. Structural factors such as lack of managerial support and unoptimized work systems also affect service performance. This study confirms the importance of affective dimensions and institutional support in shaping responsive and effective administrative services to student needs. The practical implications of these findings encourage the need for strengthening user-based service systems and excellent service training for school administration personnel.